The moorings of Mackerel Sky: a novel (Hyperion Avenue, 2024)
They say Mackerel Sky was founded when Captain Burrbank first saw Nimuë the Mermaid and forgot the sea. Stricken by love, he moored his tall ship and made camp on the highest cliff, hoping to forever gaze upon her beauty. That camp became a settlement, the settlement a town, the town a community both blessed and cursed by their tempestuous affair. Three hundred years later, the legend of the Mermaid and the Captain who loved her still invigorates and haunts the inhabitants of the small Maine lobstering town. Take gruff widow Myra Kelley, who finds herself the de facto guardian of Leo Beale and knows his drunken antics are really attempts to escape an opiate-addicted mother and her boyfriends. Or Derrick Stowe, the town's star pitcher, who wants nothing more than to read his mother's musings on mermaids, write poetry to his secret boyfriend, and come out to his father, though he will learn how devastatingly small small towns can be. Or the oft-institutionalized Manon Perle, whose gorgeous, detailed quilts of the Mackerel Sky legend belie the terrible pain of--as she claims--having given her only child to the women in the waves. In this close-knit town famous for its infamous mermaids, community is built through love and lore--willful elements that the townsfolk will have to harness if Mackerel Sky is to endure for another three hundred years.